Implementation of Digital Modules in STEM - Project Based Learning to improve Literacy and Numeracy of Middle School Students - Ferdiani, Rosita Dwi (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2024)
The focus of this research is to describe the implications of literacy-numeracy through digital-based learning (e-modules) and STEM Project Based Learning. This research is a quasi-experimental research with a Post-test-Only Control-Group design. This experimental research examines the implications of using digital modules (e-modules) and STEM Project-Based Learning to improve students' literacy and numeracy skills. The population of this study was class VIII junior high school students in East Java, Indonesia. Meanwhile, the research sample consisted of 66 students in classes VIII A and VIII B. Data analysis was carried out in two stages, namely prerequisite test analysis and hypothesis testing. The research results show implications for improving the literacy and numeracy skills of class VIII students when using digital modules and STEM Project Based Learning. Learning using digital modules with STEM – Project Based Learning positively optimizes Literacy – Numeracy abilities in junior high school students. The novelty in this research is 1) developing a digital module (E-Module) based on STEM Project-Based Learning for junior high school statistics material, which can be accessed via laptop or smartphone. 2) The implications of using digital modules (E-modules) based on STEM Project-Based Learning to improve literacy and numeracy skills in junior high school students were found.